Planned and Organized Deficit Spending (PODS) - Sahgal, Vidur (Digital Repository of Theses, 2024)
This is the first time that “Planned and Organized” has been added to the words “Deficit Spending”. Modern Monetary Theory (Mitchell, 2014, 2022; Mosler, Mitchell and Watts, 2019), a comparable alternative, originally sourced to Australian economist Bill Mitchell and developed further by him, Warren Mosler, and L. Randall Wray (Wray, 2019) way back in 1992, and Professor Stephanie Kelton’s book published in June 2020 called “The Deficit Myth” (Kelton, 2021), came close to realizing PODS (Sahgal, 2022), but the major difference between PODS and MMT was that MMT still believed in taxes, whereas PODS does not. Planned and Organized Deficit Spending (PODS) is an extension of the Distributed Equilibrium Allowable Deficit Spending Theory (DEADS). It says that deficit spending can be planned and organized in a way that could make taxes unnecessary and reduce capital shortages and market fluctuations (inflation or deflation). About DEADS (PODS original avatar, followed by OPDS, and now finally PODS), ‘allowable’ meant subject to the resources available other than money. Instead of ‘equilibrium’, resources available and produced for an economy’s population in each period were the critical requirement. This would gradually be built up to a sustainable saturation level of supply for any given product, service, or agro in an economy. Assuming the supply lags away, this implies that eventually, any product introduced into the economy can immediately, or gradually, achieve full and sustainable supply; therefore, ‘saturation’ is the more important target. PODS will not cause any displacement of relevant current personnel. The economic and commerce sectors will require millions of additional personnel, thereby creating more employment opportunities. New roles would require minimal training in the theory. The subject of Economics has its head underground amidst sophisticated math and statistical methods and analysis that give the impression, like to an ostrich, that everything is going well mathematically with one’s head underground but not at ground level. Every time someone blames the subject, math becomes even more complicated and sophisticated while serving no real purpose. To prove PODS theory, there is no need for rigorous mathematics; rather, economists should understand the logic of PODS: the Liabilities of issued E-Digital Cash are balanced with Assets made from this E-Digital Cash. Maybe after reading PODS, the math and statistical analysis, along with other econometric and regression analysis tools, will be able to manage economics as a subject where all of us, as economists, settle the entire world. It is no longer “Economics” or home accounts and finances; it is “Arthshastra—the meaning of an economic or commercial decision, at any given moment, based on mutually acceptable exchange.